Oil Price Fluctuation and Their Impact on Indonesia Manufacturing Industry - Nia, Cholida Ana; Aminata, Jaka (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2022)
This study analyzes the effect of crude oil price fluctuations using the model approach of Fukunaga et al (2009) where crude oil price fluctuations are influenced by several components such as oil supply shocks, global demand shocks, and oil-specific demand shocks. Then analyze the effect of each component on the aggregate industry production index, food, beverage and tobacco industry production index, chemical and goods from chemical raw materials, petroleum, rubber and plastic industry production index, metal, non-machinery and equipment production index. The research method is VAR in difference and the analysis methods are Granger causality test, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD). Global demand shocks and oil-specific demand shocks have a significant and positive effect on crude oil prices, while oil supply shocks have no significant effect. Oil-specific demand shocks have a significant effect on aggregate industry production index variables, while oil supply shocks and global demand shocks have no significant effect. The decomposition variables of oil price fluctuations, namely oil supply shocks, global demand shocks, oil-specific demand shocks, have no significant effect on the food, beverage and tobacco industry production index chemical and goods from chemical raw materials, petroleum, rubber and plastic industry production index, metal, non-machinery and equipment production index of metal, non-machinery and equipment.